EVALUASI PROGRAM PEMBINAAN KELEMBAGAAN PETANI DI KABUPATEN MAHAKAM ULU - Wigbertus, Rony; Idris, Adam; Rande, Santi (Jurnal Administrative Reform, 2024)
The purpose of this study is to find out and analyze the evaluation of the farmer institutional development program from organizational, managerial and entrepreneurial abilities and the supporting factors and inhibiting factors of the evaluation of the farmer institutional development program in Mahakam Ulu Regency. This research uses a mixed method, namely a series of qualitative and quantitative approaches. This research is focused on evaluating the farmer institutional development program in Mahakam Ulu Regency in farmers' managerial, organizational and entrepreneurial development. This study shows that the results of the evaluation of the farmer institutional development program are feasible to continue. This is measured by the efficiency aspect of the farmer institutional development program, which is measured by the optimal use of resources, which is considered good overall on the efficiency of the farmer institutional development program. The effectiveness of the farmer institutional development program in Mahakam Ulu is still categorized as effective (sound). The responsiveness of the farmer institutional development program in Mahakam Ulu Regency is still categorized as good. The adequacy of the farmer institutional development program in Mahakam Ulu is still categorized as good. The distribution of farmer institutional development programs is also quite good. The accuracy of the farmer institutional development program in Mahakam Ulu is still categorized as good.